2014
DOI: 10.1371/journal.pone.0099627
|View full text |Cite
|
Sign up to set email alerts
|

Global Genome Response of Escherichia coli O157∶H7 Sakai during Dynamic Changes in Growth Kinetics Induced by an Abrupt Temperature Downshift

Abstract: Escherichia coli O157∶H7 is a mesophilic food-borne pathogen. We investigated the growth kinetics of E. coli O157∶H7 Sakai during an abrupt temperature downshift from 35°C to either 20°C, 17°C, 14°C or 10°C; as well as the molecular mechanisms enabling growth after cold stress upon an abrupt downshift from 35°C to 14°C in an integrated transcriptomic and proteomic analysis. All downshifts caused a lag period of growth before growth resumed at a rate typical of the post-shift temperature. Lag and generation tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 91 publications
(149 reference statements)
4
18
0
Order By: Relevance
“…The strain of E. coli O157:H7 Sakai (19, 20) used in this study was provided by Carlton Gyles (Guelph, Canada). A stock culture was maintained at −80 °C and was cultivated by plating onto brain-heart infusion (BHI) agar (Thermo Scientific, Waltham, MA, CM225) and incubating at 37 °C for 24 h. An isolated colony was inoculated into 25 ml of BHI broth and incubated at 37 °C for 20 h. The resulting broth culture was kept at 4 °C and used as a “working” culture within a week.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The strain of E. coli O157:H7 Sakai (19, 20) used in this study was provided by Carlton Gyles (Guelph, Canada). A stock culture was maintained at −80 °C and was cultivated by plating onto brain-heart infusion (BHI) agar (Thermo Scientific, Waltham, MA, CM225) and incubating at 37 °C for 24 h. An isolated colony was inoculated into 25 ml of BHI broth and incubated at 37 °C for 20 h. The resulting broth culture was kept at 4 °C and used as a “working” culture within a week.…”
Section: Methodsmentioning
confidence: 99%
“…The T-profiler t test based method of Boorsma et al (33) was performed on the log 2 expression ratios, as previously described (19, 20), to determine changes in overall expression of a predefined set of proteins cold osmotic shock.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests a "window" of cell susceptibility in which novel "intervention" strategies might be applied to more successfully reduce E. coli levels on carcasses. Reinforcing these observations, King et al (2014) and Kocharunchitt et al (2014) used an integrated transcriptomic and proteomic approach to study the physiological response of E. coli to a rapid downshift in temperature or water activity, respectively. Those studies showed distinct proteomic and transcriptomic responses of E. coli to abrupt temperature or water activity shifts, and identified potential susceptibilities to oxidative stress of E. coli during exposure to combined chilling and osmotic stress conditions.…”
Section: Discussionmentioning
confidence: 91%